Epidemiological Aspects of Monitoring the Sensitivity of Staphylococcus aureus Strains - N. Kh. Otamuratova; G. K. Abdukhalilova; D. R. Akhmedova; Yu. A. Tursunova (Антибиотики и Химиотерапия, 2025)
Growing concern about the emergence of resistance in clinically significant pathogens has led to the establishment of a number of surveillance programs to monitor the actual level of resistance at local, regional, and national levels. The aim of the study is to analyze the antibiotic susceptibility of Staphylococcus aureus in infections of various localizations in pediatric practice. Material and methods. The study was conducted using biological material from patients (blood, urine, sputum, pharynx, etc.) received by the bacteriological laboratory of the Republican Scientific and Practical Medical Center of Pediatrics (P4) from different departments, for the period from January 2020 to December 2022. Nutrient media and discs with antimicrobial drugs manufactured by Himedia (India) were used. Results. The analysis of the sensitivity of Staphylococcus aureus strains showed that in the pilot institution of the Republican Specialized Scientific Practice Medical Center, the local antibiotic profile of the Staphylococcus aureus strains has the following picture: 98.3% are resistant to penicillin, 62.5% are resistant to erythromycin, 52.6% are resistant to clindamycin, 48.7% are resistant to cefoxitin, which indicates resistance to all β-lactam antimicrobial drugs, 16.2% are resistant to ciprofloxacin, 15.4% are resistant to levofloxacin, 7.7% are resistant to linezolid, and 5.3% are resistant to amikacin. Conclusion. In the general structure of microorganisms of the hospital, Staphylococcus aureus strains prevailed (50%). A high level of sensitivity to amikacin (94.7%), and rifampicin (94.3%), as well as high resistance to penicillin (98.3%) and cefoxitin (48.7%), was noted when studying the sensitivity of Staphylococcus aureus strains isolated from patients with various diseases from various biological materials.